2005
DOI: 10.1097/01.brs.0000162623.48058.8c
|View full text |Cite
|
Sign up to set email alerts
|

Lower Dose of rhBMP-2 Achieves Spine Fusion When Combined With an Osteoconductive Bulking Agent in Non-human Primates

Abstract: This study shows the importance of carrier optimization and final implant protein concentration for the successful delivery of rhBMP-2. By combining the properties of the ACS with the CRM, the required dosage of rhBMP-2 was diminished by more than 3-fold in the non-human primate model. This finding suggests that the currently available concentration of rhBMP-2 (1.5 mg/mL) could be successful for achieving posterolateral spine fusion when combined with an osteoconductive bulking agent that can support the induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 28 publications
(27 reference statements)
1
50
1
Order By: Relevance
“…9,43 Pre-clinical studies have also suggested that because of its favorable binding properties to osteoinductive growth factors such as rhBMP-2, the dose required to achieve successful bony fusion is effectively reduced. 44,45 To this end, recent studies have demonstrated that a 10-15% hydroxyapatite composition in a ceramic carrier is ideal for stem cell adhesion and osteoblastic differentiation. 46,47 In comparison, Grafton 1 is a DBM processed from human tissue into bone fibers combined with glycerol (79-85% content) to achieve a putty-like consistency.…”
Section: Discussionmentioning
confidence: 99%
“…9,43 Pre-clinical studies have also suggested that because of its favorable binding properties to osteoinductive growth factors such as rhBMP-2, the dose required to achieve successful bony fusion is effectively reduced. 44,45 To this end, recent studies have demonstrated that a 10-15% hydroxyapatite composition in a ceramic carrier is ideal for stem cell adhesion and osteoblastic differentiation. 46,47 In comparison, Grafton 1 is a DBM processed from human tissue into bone fibers combined with glycerol (79-85% content) to achieve a putty-like consistency.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In addition, biomechanical differences have been largely stated and reports concerning differential biological responses -e.g. baboons seem to be hypersensitive to the administration of bone morphogenic proteins 28 contribute to the fact that NHPs do not attain a valid consensus as providing a first choice model, compared to other large animals. 7 As stated, a wide range of animal models is available not only for fundamental, feasibility and bioactivity bonerelated biomedical research, but also for preclinical testing.…”
Section: Selection Of Animal Species -The Relevance Of Rodentsmentioning
confidence: 99%
“…However, non-unions are seen in the patient material. In the event of forming stable bridging bone in a bone transplant, different bone morphogenetic proteins are active in different time periods in a cascade reaction and perhaps other preparations (Barnes et al 2005, Vaccaro et al 2005a and other bone formation promoters (Boden et al 2002) can bring further improvement.…”
Section: Lumbar Segmental Mobility Adjacent To Fusionmentioning
confidence: 99%